1983
DOI: 10.1177/000456328302000601
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol: A Better Measure of Adrenal Cortical Function than Serum Cortisol

Abstract: SUMMARY Salivary cortisol concentration was found to be directly proportional to the serum unbound cortisol concentration both in normal men and women and in women with elevated cortisolbinding globulin (CBG). The correlation was excellent in dynamic tests of adrenal function (dexamethasone suppression, ACTH stimulation), in normals and patients with adrenal insufficiency, in tests of circadian variation and randomly collected samples. Women in the third trimester of normal pregnancy exhibited elevated salivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
367
3
14

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(396 citation statements)
references
References 18 publications
12
367
3
14
Order By: Relevance
“…The discrepancy between salivary and plasma results may be explained by diurnal-related variations. Indeed, the influence of housing on salivary cortisol was observed at 0700 h but not at 1100 h, whereas blood samples were drawn between 0830 and 0930 h. Moreover, salivary cortisol is more tightly linked to the free fraction of circulating cortisol than to the total concentration of cortisol that was measured in this study (Vining et al, 1983;Perogamvros et al, 2010).…”
Section: Discussionmentioning
confidence: 70%
“…The discrepancy between salivary and plasma results may be explained by diurnal-related variations. Indeed, the influence of housing on salivary cortisol was observed at 0700 h but not at 1100 h, whereas blood samples were drawn between 0830 and 0930 h. Moreover, salivary cortisol is more tightly linked to the free fraction of circulating cortisol than to the total concentration of cortisol that was measured in this study (Vining et al, 1983;Perogamvros et al, 2010).…”
Section: Discussionmentioning
confidence: 70%
“…In our study, late-night plasma and salivary cortisol levels showed a positive correlation. In fact, salivary cortisol concentrations are directly proportional to serum unbound cortisol concentration [18]. our data, combined with a simple, stress-free, and non-invasive collection procedure, suggest that the salivary cortisol level is a more appropriate measure for the clinical assessment of adrenocortical function than the plasma cortisol level.…”
Section: Acknowledgmentsmentioning
confidence: 69%
“…11 The rate of appearance of cortisol in the saliva following an increase in the blood level is very rapid, , 5 min. 12 Studies in healthy volunteers and for the evaluation of patients with hypothalamus-pituitary-adrenal axis disease have showed an excellent correlation between free or unbound serum and salivary cortisol levels, although the relationship is nonlinear and correlation is more closely related at lower levels (when total serum concentration is , 16.3 m g/dL). [13][14][15] We evaluated the correlation between salivary cortisol and total serum cortisol with free serum cortisol levels in adult medical intensive care patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the mean salivary cortisol was higher than the mean free serum cortisol, without reaching statistical signifi cance. 12,19 Prior salivary cortisol studies were performed in healthy volunteers and not ICU patients with septic shock in whom normal adrenal function and cortisol concentrations are still unknown. It has been postulated that salivary cortisol determination is more useful, especially after ACTH stimulation test, since it refl ects immediate changes in the unbound serum cortisol without being affected by the CBG or albumin concentration.…”
Section: Discussionmentioning
confidence: 99%